The Antecedents and Consequences of Firm-Level Entrepreneurship: The State of the Field - Zahra, Shaker A.; Jennings, Daniel F.; Kuratko, Donald F. (Entrepreneurship Theory and Practice, 1999)
Empirical research into firm-level entrepreneurship spans over a quarter of a century. This article reviews the current state of this research by identifying key trends in 45 published empirical studies; examining the key issues addressed and methods used to examine them; and outlining six key areas that need greater attention in future research.